2009
DOI: 10.1097/qad.0b013e328331910c
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-related and non-AIDS-related mortality in the Asia-Pacific region in the era of combination antiretroviral treatment

Abstract: Introduction Although studies have shown reductions in mortality from AIDS after the introduction of combination antiretroviral treatment (cART), little is known about cause-specific mortality in low income settings in the cART era. We explored predictors of AIDS and non-AIDS mortality and compared cause-specific mortality across high and low income settings in the Asia Pacific region. Methods We followed patients in the Asia Pacific HIV Observational Database from the date they started cART (or cohort enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 37 publications
5
32
0
4
Order By: Relevance
“…This finding was rather surprising as we expected the opposite, given our definition of morbidity as number of concurrent illnesses at the time of death. In a study on AIDS and non-AIDS mortality in the era of antiretroviral therapy by Falster et al 16 , they found that of 215 deaths, 89 were AIDS related, 97 non-AIDS related and 29 were unknown. They found age greater than 50 years and CD4 counts > 100 increased the risk of non AIDS deaths (HR 4.99) whereas CD4 ≤100 and viral load >10,000 increased the risk of AIDS deaths (HR 4.21).…”
Section: Discussionmentioning
confidence: 98%
“…This finding was rather surprising as we expected the opposite, given our definition of morbidity as number of concurrent illnesses at the time of death. In a study on AIDS and non-AIDS mortality in the era of antiretroviral therapy by Falster et al 16 , they found that of 215 deaths, 89 were AIDS related, 97 non-AIDS related and 29 were unknown. They found age greater than 50 years and CD4 counts > 100 increased the risk of non AIDS deaths (HR 4.99) whereas CD4 ≤100 and viral load >10,000 increased the risk of AIDS deaths (HR 4.21).…”
Section: Discussionmentioning
confidence: 98%
“…A follow-up study by Achhra et al concluded that this mean CD4 cell count difference translated to minimal clinical significance in terms of mortality and new AIDS-defining illness [22]. A comprehensive analysis of AIDS-related and non-AIDS-related mortality in AHOD and TAHOD also reported little evidence of differing hazard ratios of mortality in TAHOD-High and TAHOD-Low relative to AHOD [24]. However, in a TAHOD-specific study, Oyomopito et al reported less favorable treatment outcomes for sites that reported less than once-yearly RNA-VL testing compared to those sites that monitored RNA-VL at least once-yearly [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately 10% of PLHIV are expected to exhaust all currently available cART options after just 25.6 years, exposing these individuals to higher mortality rates [13,14]. In Fig.…”
Section: Resultsmentioning
confidence: 99%